The pattern of upbringing of middle to lower economic families in urban communities - Diva Oktaviana (Indonesian Journal of Social Sciences, 2020)
The purpose of writing this article is to examine the way parenting can influence the growth of attitudes and character in children from families in lower middle economic classes. By studying the parenting, the most appropriate parenting for children’s growth and development. The study was conducted on the social figures around children, especially parents and teachers who can understand every pattern of development that occurs in children in a city. This research utilized in-depth interviews and observation methods in order to identify the  meeting point that the best parenting pattern is democratic parenting. Therefore, the inculcation of attitudes towards children from an early age must indeed be carried out to support the implementation of democratic parenting. Family and school are the social institutions that are interlocking and have a reciprocal relationship since both hold an important role for the growth and development of children. Having a synergistic relationship and becoming the social control for children are the essential key in improving the children’s quality in the future. Economic limitations are not an obstacle to the fulfillment of the social role held by parents and schools. Precisely with this awareness, it is expected that families can become more aware of the impacts resulting from parenting mistakes. Children who will become the future of the family will be saved. Social mobility is also highly likely to occur when parenting is properly implemented.